2021
DOI: 10.1177/17562848211014817
|View full text |Cite
|
Sign up to set email alerts
|

Immune response against Clostridioides difficile and translation to therapy

Abstract: The pathogenesis of Clostridioides difficile infection (CDI) has largely been attributed to the action of two major toxins – A and B. An enhanced systemic humoral immune response against these toxins has been shown to be protective against recurrent CDI. Over the years, fully human monoclonal antibodies against both of these toxins have been developed in an attempt to counter the increasing incidence of recurrent CDI. Clinical trials conducted to evaluate the efficacy of anti-toxin A monoclonal antibody, actox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 64 publications
(92 reference statements)
0
10
0
Order By: Relevance
“…Though multiple clinical trials have shown varying levels of efficacy of bezlotoxumab, results in humans are not as encouraging as in the animal models (Leav et al, 2010;Lowy et al, 2010;Wilcox et al, 2017). Nevertheless, bezlotoxumab treatment results in an absolute reduction in recurrence of 10% (27% vs. 17%) with a relative recurrence rate reduction 38% lower than standard-of-care antimicrobial treatment alone (Sehgal and Khanna, 2021).…”
Section: Toxin-based Immunization Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Though multiple clinical trials have shown varying levels of efficacy of bezlotoxumab, results in humans are not as encouraging as in the animal models (Leav et al, 2010;Lowy et al, 2010;Wilcox et al, 2017). Nevertheless, bezlotoxumab treatment results in an absolute reduction in recurrence of 10% (27% vs. 17%) with a relative recurrence rate reduction 38% lower than standard-of-care antimicrobial treatment alone (Sehgal and Khanna, 2021).…”
Section: Toxin-based Immunization Strategiesmentioning
confidence: 99%
“…Another type of immunization is the direct administration of monoclonal antibodies. The best known example of this is bezlotoxumab, a monoclonal anti-TcdB antibody, which has recently been reviewed (Sehgal and Khanna, 2021). It is believed that upon intravenously administration at the end of antimicrobial therapy of CDI, the antibody is transported to the luminal compartment of the intestines through paracellular transport.…”
Section: Toxin-based Immunization Strategiesmentioning
confidence: 99%
“…[145][146][147] The occurrence of C. difficile infection (CDI) is associated with the use of antibiotics, especially clindamycin or broad-spectrum antibiotics such as third to fourth generation cephalosporins, and uoroquinolones. 148 The exposure to antibiotics oen results in an altered and unfavorable gut microbiota composition, 149 leading to the proliferation of C. difficile and subsequently to the production of toxins. 150 Other risk factors for CDI are older age, inammatory bowel disease, multimorbidity, and immunosuppression.…”
Section: Clostridioidesmentioning
confidence: 99%
“…As there are recent and excellent reviews on the immune response to C. difficile [ 10 , 42 , 43 ], in this section, we present the main characteristics of this host-pathogen interaction.…”
Section: Essential Concepts Of the Immune Response During CDImentioning
confidence: 99%